A systematic literature review on maturity models for information systems in higher education institutions - João Vidal de Carvalho (2019)
Maturity models have been introduced over the last five decades as guides and references for information system (IS) management in organizations from different sectors. In the education sector, maturity models have also been used to evaluate higher education institutions (HEIs) across several dimensions, such as information and communication technology (ICT), management, process management, course curricula, course/HEI accreditation, e-/m-learning, online courses and pedagogical strategies. In fact, HEIs are faced with enormous complexity due to the specificity and quantity of their processes. Based on the guidelines concerning a methodology for a systematic literature review, the maturity models of different subareas of education are identified and categorized in this paper. For each maturity model associated with HEIs’ ISs, the appropriate methodology for development and validation is identified, as well as the scope, stages and their dimensional characteristics. This study highlights the need to develop an IS maturity model that supports HEIs in their core business activities and management.